Formulation and development of floating multiple-unit minitablets of Nimodipine without using a gas-generating agent: in vitro and in vivo characterization - M. Panda; M. E. B. Rao; C. N. Patra; J. Panda; K. C. Panigrahi; G. Patro (SpringerOpen, 2020)
Abstract Background Floating drug delivery systems have been reported for different active pharmaceutical ingredients as single-unit tablets with gas-generating agents. In this present research, the formulation of floating multiple-unit minitablets of Nimodipine without using gas-generating agent was attempted with an objective of increased residence time, sustain-release and improved oral bioavailability. Solid dispersion with different ratios (1:0.5, 1:1, 1:1.5, 1:2, 1:2.5) of drug with the lipophilic carrier such as Compritol ATO 888, Gelucire 43/01, G39/01 and Precirol ATO 05 was formulated using melt granulation technique. The adsorbent Sylysia 350 to lipophilic carrier is maintained at 1:1. The granules were compressed into minitablets weighing 15 mg and were filled into a '0' size capsule. Results Differential scanning calorimetry study justified no interaction of the drug with excipients. The formulations which exhibited desirable flow property, floating lag time less than 1 min and floating time of 12 h were further characterized for various post-compression parameters. The optimized single-dose (capsule) of floating multiple-unit minitablets of Nimodipine consisting of 60 mg of drug, 120 mg of G43/01 and 120 mg of Sylysia 350 showed an average of floating lag time within 24.48 s, floating time of 14.32 h and sustained-release up to 12 h. Pharmacokinetic study of the optimized formulation (F9) showed nearly 2.5 times increase in area under the curve with increased residence time in comparison to aqueous suspension of Nimodipine. The stability study revealed no significant change in various parameters before and after storage. Conclusion Hence, gelucire 43/01-based multiple-unit minitablets of Nimodipine can be considered a promising approach for sustaining the drug release with gastric retention for 12 h without using gas-generating agent.